Perspectives of treating swine manure biodigestors in projects of carbon capture in Brazil - Marques, Fernando Mario Rodrigues; Parente, Virgínia; Silva, Carlos Cezar da; Grimoni, José Aquiles Baesso; Frimaio, Geslaine (Revista Agrogeoambiental, 2010)
The Clean Development Mechanism (CDM) projects proposed in the Kyoto Protocol constitute an interesting way of protecting the environment and at the same time promoting sustainable economic development in emerging economy countries. Possible CDM projects include the treatment of swine manure using biodigestion, which would provide an opportunity for Brazil to actively participate in the carbon credits market. Brazil is currently the world’s third leading swine producer (36 million animals). This study aims to demonstrate that the treatment of swine manure using bio digestion can minimize environmental impact and also contribute to reducing carbon dioxide emissions into the atmosphere by approximately 19 million tons per year, generating around US 78 million in carbon credits for Brazil annually.